2022
DOI: 10.3390/ijerph19116679
|View full text |Cite
|
Sign up to set email alerts
|

Does Governance Quality Matter for the Selection of Policy Stringency to Fight COVID-19?

Abstract: Independent of different national conditions, an indisputable fact is that the worldwide governments should play a role in fighting the ongoing COVID-19. To make clear the determinants of government response to tackle COVID-19, I investigate the impact of governance quality. To do so, I newly create an overall governance index based on six dimensions of Worldwide Governance Indicators (WGI) from the World Bank to proxy governance quality. I regress the overall governance index with controls on the stringency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…An increasing number of studies have highlighted the significance of governance in urban resilience improvement ( Wang, 2022 ; Yan & Cao, 2022 ). This paper constructed the CLD of governance resilience from the perspective of the emergency management of local governments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of studies have highlighted the significance of governance in urban resilience improvement ( Wang, 2022 ; Yan & Cao, 2022 ). This paper constructed the CLD of governance resilience from the perspective of the emergency management of local governments.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have acknowledged that governments play an essential role in the response of large-scale public health events like COVID-19 ( Wang, 2022 ), and their governance quality and policies have been investigated. Shi et al (2022) analyzed the governance resilience of urban communities with different geographical locations and social classes during the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, despite the measures taken to alleviate the crisis, efforts were made to reduce its negative social and economic effects, but the loss of well-being was felt in many cases [ 17 ]. Previous studies have shown that when national governments tend to adopt stricter measures to fight against COVID-19, the outcomes can be more meaningful [ 45 47 ]. Risks can be more easily counteracted through institutional transparency, open communication between stakeholders and closeness to citizens.…”
Section: Literature Reviewmentioning
confidence: 99%